Students’ Perception on Character Education in the Novel Calabai - Nahdhiyah Nahdhiyah; Syahruni Junaid; Ahmad Muzzammil (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
This study aims to find the value of character education in Novel ‘Calabai’ through students’ perception. This study also accustoms Literature students doing analysis and finding the surface and the latent meaning in a literary work. This study reveals that  literary work not only displays a beautiful word string but beyond it there are meanings of life education. This study uses descriptive qualitative method where this study described the results of students’ perception about character education in novel “Calabai”. Data resource of this research is the novel Calabai by Pepy Al Bayquni. Coding sheet is used to code or to take a note of four students’ overview, understanding, thinking or interpretation on values of character education in novel Calabai. Three stages of analyzing data: deconstruction, interpretation, and reconstruction. There are 91 data contains character education. The  91 data are spreaded into 32 values of  character education.